2021
DOI: 10.1001/jamainternmed.2021.5726
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nonfatal Myocardial Infarction as a Surrogate for All-Cause and Cardiovascular Mortality in Treatment or Prevention of Coronary Artery Disease

Abstract: IMPORTANCEAlthough nonfatal myocardial infarction (MI) is associated with an increased risk of mortality, evidence validating nonfatal MI as a surrogate end point for all-cause or cardiovascular (CV) mortality is lacking.OBJECTIVE To examine whether nonfatal MI may be a surrogate for all-cause or CV mortality in patients with or at risk for coronary artery disease.DATA SOURCES In this meta-analysis, PubMed was searched from inception until December 31, 2020, for randomized clinical trials of interventions to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 180 publications
2
30
0
1
Order By: Relevance
“…Thus, as in the case of bleeding, the occurrence of MI appears to be a marker of worse cardiovascular risk profile which may be an underlying factor for increased risk for mortality. A recent large meta-analysis of randomized clinical trials of interventions to treat coronary artery disease suggested that nonfatal MI appears not to be a surrogate for all-cause or cardiovascular mortality [25]. Second, in the current study, MI included spontaneously occurring (type 1) and periprocedural MI based on the measurements of high-sensitivity cardiac troponins.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, as in the case of bleeding, the occurrence of MI appears to be a marker of worse cardiovascular risk profile which may be an underlying factor for increased risk for mortality. A recent large meta-analysis of randomized clinical trials of interventions to treat coronary artery disease suggested that nonfatal MI appears not to be a surrogate for all-cause or cardiovascular mortality [25]. Second, in the current study, MI included spontaneously occurring (type 1) and periprocedural MI based on the measurements of high-sensitivity cardiac troponins.…”
Section: Discussionmentioning
confidence: 96%
“…The authors of a meta-analysis assessed trial data spanning 50 years and concluded that non-fatal myocardial infarction is not a robust surrogate outcome for mortality 1…”
Section: Summary Sentencementioning
confidence: 99%
“…This meta-analysis of clinical trial data assessed whether non-fatal myocardial infarction (MI) is a robust surrogate outcome for all-cause or cardiovascular mortality in people with, or at risk of, coronary artery disease 1. The authors searched for randomised controlled trials (RCTs) of interventions to treat or prevent coronary artery disease published in three journals ( The New England Journal of Medicine, Journal of the American Medical Association or The Lancet ).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter may be explained by the improved management of spontaneous MIs, which results in reduced fatality rates than several decades ago. Also, a recent meta-regression analysis of large coronary artery disease trials showed that non-fatal MI is a poor surrogate outcome for all-cause or cardiovascular mortality [6] . We have to note as well that spontaneous MI was not a pre-specified endpoint of any of the eligible trials.…”
mentioning
confidence: 99%